WUJUD PEMBELAJARAN PRINSIP KESANTUNAN BERBAHASA MAHASISWA PRODI PENDIDIKAN BAHASA DAN SASTRA INDONESIA - Wahyu Ningsih; Nur Khadijah Razak; Halijah H (Jurnal Pendidikan Sang Surya, 2021)
Abstract: This study discusses the form of learning to the principles of language politeness in the Indonesian Language and Literature Education Study Program Students, Universitas Muhammadiyah Makassar. This research was conducted in two stages, namely the data collection stage and the data analysis stage. The data collection stage was carried out through field research to obtain primary data using observation techniques and notes on the data card, while at the data analysis stage the authors used qualitative descriptive analysis. This analysis is used to obtain an overview of the form of maximizing the application of student conversations. The results obtained show that adherence to the principles of politeness is still a concern of students when speaking well with fellow students, especially towards lecturers. This indicates that the supporting factors for the realization of good communication are well understood and realized. The supporting factors are the conversation situation, the object being discussed, the individual language users involved, being able to see the appropriateness and accuracy of the use of vocabulary in the conversation. The use of maxims in conversation through the principles of language politeness put forward by Leech, including the maxim of wisdom, the maxim of acceptance, the maxim of generosity, the maxim of humility, the maxim of agreement and the maxim of sympathy.